GIS-Based Identification Of Overloaded Distribution Transformers & Calculation Of Technical Electric Power Losses - Ahmad, Awais; Akbari, Abolghasem; Iqbal, Javed (Penerbit UMP, 2015)
This research was designed with the objectives to develop a standalone GIS application for electrical power distribution network companies having the capability of loss calculation as well as identification of overloaded transformers. For this purpose Hilal Road feeder in Faisalabad Electric Supply Company (FESCO) was selected as study area. An extensive GPS survey was conducted to identify each consumer, linking it to secondary pole of the transformer, geo-referencing equipments and documenting conductor sizes. To identify overloaded transformer, accumulative kilowatt hour (kWh) reading of consumer on transformer was compared with threshold kWh. Technical losses of 11kV power transformer and 220V lines were calculated using the data from substation and resistance of the network calculated from the geo-database. To automate the process a standalone GIS application was developed using ArcObjects with engineering analysis capabilities. The application uses GIS database developed for 11kV and 220V lines to display and query spatial data and present results in the form of graphs. The result shows that about 14% of technical loss on both high tension (HT) and low tension (LT) network while about 4 out of 15 general duty transformers were found overloaded. The study shows that GIS can be a very effective tool for distribution companies in management and planning of their distribution network.